JATIDIRI MANUSIA BERDASARKAN FILSAFAT TINDAKAN HANNAH ARENDT PERSPEKTIF FILSAFAT MANUSIA: RELEVANSI DENGAN PELANGGARAN HAM TAHUN 1965-1966 DI INDONESIA - Astrid Veranita Indah (Jurnal Filsafat "WISDOM", 2015)
The essential problem of human rights violation is a matter of human life. The issue raises many new problems, including the trauma suffered by victims and guilty feelings experienced by perpetrators. Some cases of human rights violation, can often be resolved by the constitutional court. Other cases cannot be solved by laws and regulations that have been established. In such cases, it requires an accomplishment by using another point of view, for example, by understanding the basic structure of human person, based on Hannah Arendt's philosophy of action. This research is a qualitative research with emphasises library research in obtaining data. Methods used in this study are hermeneutics, and heuristics. The formal object is human person that is part of philosophy of human. Theory of human person which is categorized into three parts, namely: the personality of human, self identity of human, and the uniqueness in the sociality of human. The result of this research is an exposure of the philosophy of human action, as an ultimate activity in the vita activa. Human beings as individuals, are body and soul; soul and mind. Self identity is understood not only as the present, but also the past and the projections of the future. Human beings develop continuously in the historicity of the time, so that each individual is unique from the others. This uniqueness colors the difference in plurality of life which is expected to keep the friendship in a community. Arendt's philosophy has been successfully answered the problem for human rights violation during the under Nazi rule. Arendt's analysis of the problem for the emphasis on the human personality-conscious thinking in a situation that tends to be authoritarian. Another analysis is the human ability to forgive, promise and build friendship. It is inspire to answer the problem for human rights violation at Indonesia upon 1965-1966. Understanding based on consciousness thinking, forgiveness, promise and friendship will break the cycle of revenge, restore social memory, and ensure the creation of rights of every citizen.